Comparing Prescriptive and Descriptive Gender Stereotypes About Children, Adults, and the Elderly - Koenig, Anne M. (Frontiers in Psychology, 2018)
Gender stereotypes have descriptive components, or beliefs about how males and females typically act, as well as prescriptive components, or beliefs about how males and females should act. For example, women are supposed to be nurturing and avoid dominance, and men are supposed to be agentic and avoid weakness. However, it is not clear whether people hold prescriptive gender stereotypes about children of different age groups. In addition, research has not addressed prescriptive gender stereotypes for the elderly. The current research measured prescriptive gender stereotypes for children, adults, and elderly men and women in 3 studies to (a) compare how prescriptive gender stereotypes change across age groups and (b) address whether stereotypes of males are more restrictive than stereotypes of females. Students (Studies 1 and 2) and community members (Study 3), which were all U.S. and majority White samples, rated how desirable it was for different target groups to possess a list of characteristics from 1 (very undesirable) to 9 (very desirable). The target age groups included toddlers, elementary-aged, adolescent, young adult, adult, and elderly males and females. The list of 21 characteristics was created to encompass traits and behaviors relevant across a wide age range. In a meta-analysis across studies, prescriptive stereotypes were defined as characteristics displaying a sex difference of d >.40 and an average rating as desirable (positive prescriptive stereotypes) or undesirable (negative proscriptive stereotypes) for male or females of each age group. Results replicated previous research on prescriptive stereotypes for adults: Women should be communal and avoid being dominant. Men should be agentic, independent, masculine in appearance, and interested in science and technology, but avoid being weak, emotional, shy, and feminine in appearance. Stereotypes of boys and girls from elementary-aged to young adults still included these components, but stereotypes of toddlers involved mainly physical appearance and play behaviors. Prescriptive stereotypes of elderly men and women were weaker. Overall, boys and men had more restrictive prescriptive stereotypes than girls and women in terms of strength and number. These findings demonstrate the applicability of prescriptive stereotypes to different age groups.